Dampak Penggunaan Handphone terhadap Proses Pembelajaran Peserta Didik di SMP Negeri 25 Padang - -, Maisardi - (Bimbingan dan Konseling, 2014)
This research is motivated by a phenomena in which learners use handphone in thelearning process. There are some learning didnât polite because used handphone to SMS theirfriend during learning process, save the pictures of adults, and when their change sportswear.Purpose of this research to describing: 1) Positive impact of using handphone that learningprocess. 2) Negative impact of using handphone that learning process in SMP Negeri 25 Padang.This research is descriptive quantitative. Population of all learners in SMP Negeri 25 Padangwith 731 people. The sampling was done by using simple random sampling. This research to thelearner as a sample consist of 88 person. The research used the questionnaire instruments. For theanalyzing the data the researcher used presentation tecniq. The result of this research to inform.The positive impact (46,59%), and the negative impact (42,05%). Based on research, theresearcher was recommendation to the learners to use the handphone well.